FASILITAS KEBUGARAN AKUATIK DI SUNTER - Arifia Arifia; Lina Purnama (Jurusan Arsitektur dan Perencanaan, 2019)
One of the contemporaneity issues of millenials is the lifestyle or millenial’s unhealthy lifestyle because they are unable to control their lifestyle. These lifestyles are influenced by advances in technology that increase the influence of globalization such as fast food and ease of fulfillment of needs such as application-based inter-service namely online motorcycle taxi and other features. These factors directly or indirectly cause millennial’s behavior patterns to be unhealthy, passive (in-active), decreased mental conditions, and much more. These behaviors have many negative effects on the physical and spiritual health conditions of millennials.Wellness aimed at the impact of 'well-being' or individual well-being. According to the CDC (Centers for Disease Control and Prevention), 'Well-being' can improve individuals or groups physical and spiritual health due to the results from who know how to live well. Therefore, 'Wellness' can provide a change towards a healthier lifestyle by presenting a pleasant and interesting impression of the mainly millennial community, the Aquatic Wellness Facility. The element of water from aquatic aspect provides relaxation, calmness, recreational atmosphere and so on that can provide a healing environment. Aquatic Wellness facilities are given the impression of recreation so that the community and millennials do physical activities with a feeling of pleasure. To get the concept of the program, the author uses the wellness criteria of Tchiki Davis, PH.D. and questionnaires that produce aquatic programs both in terms of physical and spiritual as well as social activities and lifestyle improvements through monitoring habits. The concept of mass composition is formed from 4 character elements of healing environment, namely water, stone, cave, and mountain. AbstrakSalah satu isu kesejamanan kaum milenial yakni gaya hidup atau lifestyle kaum milenial yang tidak sehat karena tidak mampu mengendalikan gaya hidup mereka. Gaya hidup tersebut dipengaruhi oleh kemajuannya teknologi, pengaruh globalisasi seperti makanan cepat saji dan kemudahan pemenuhan kebutuhan seperti pelayanan antar berbasis aplikasi yakni ojek online dan features lainnya. Faktor-faktor tersebut secara langsung atau tidak langsung menyebabkan pola perilaku kaum Milenial menjadi tidak sehat, pasif (in-active), kondisi mental yang menurun, dan masih banyak lagi. Dengan begitu, perilaku tersebut memberikan banyak dampak negatif terhadap kondisi kesehatan jasmani dan rohani kaum milenial. Wellness berfokus pada dampak dari ‘well-being’ atau kesejahteraan individu. Menurut CDC (Centers for Disease Control dan Prevention), ‘Well-being’ dapat meningkatkan kesehatan jasmani dan rohani individu atau kelompok akibat hasil dari menjalani kehidupan dengan baik. Oleh karena itu, ‘Wellness’ dapat memberikan pergeseran terhadap gaya hidup menjadi lebih sehat dengan menghadirkan kesan menyenangkan dan menarik masyarakat terutama milenial yakni Fasilitas Kebugaran Akuatik. Unsur air dari segi akuatik memberikan relaksasi, ketenangan, suasana rekreasi yang dapat memberikan lingkungan menyenangkan untuk penyembuhan. Fasilitas kebugaran akuatik diberikan kesan rekreasi sehingga masyarakat maupun kaum milenial melakukan kegiatan kebugaran dengan perasaan senang. Untuk mendapatkan konsep program tersebut, penulis menggunakan kriteria wellness dari Tchiki Davis,PH.D. dan kuesioner yang menghasilkan program akuatik baik dari segi jasmani dan rohani serta kegiatan sosial dan perbaikan gaya hidup melalui monitoring habits. Konsep gubahan massa terbentuk dari 4 karakter unsur healing environment yakni air, batu, goa, dan gunung.